Physics affecting heavy impurity migration in tokamaks: Benchmarking test-ion code ASCOT against TEXTOR tracer experiment. (May 2019) - Weckmann, A.; Kurki-Suonio, T.; Särkimäki, K.; Romazanov, J.; Kirschner, A.; Hakola, A.; Airila, M.; Kreter, A.; Brezinsek, S.
Highlights : ASCOT simulations of TEXTOR molybdenum transport experiments were carried out. Central and SOL plasma parameters were varied to study the impact on high-Z impurity transport in the simulations. Toroidal plasma movement, either within the LCFS or as SOL flow, is negligible. SOL profile and marker starting energy have modest impact on deposition. Source distribution has a large impact in combination with radial electric field profiles. The E ⇀ × B ⇀ drift has the highest impact on the deposition profiles. Abstract: Erosion, transport and deposition of wall impurities are major concerns in future magnetic fusion devices, both from the perspective of the fusion plasma and the machine wall. An extensive study on molybdenum transport and deposition performed in the TEXTOR tokamak yielded a detailed deposition map that is ideal for benchmark deposition studies. A qualitative benchmark is attempted in this article with the ASCOT code. We set up a full 3D model of the TEXTOR tokamak and studied the influence of different physical mechanisms and their strengths on molybdenum deposition patterns on the simulated plasma-facing components: atomic processes, Coulomb collisions, scrape-off layer (SOL) profiles, source distribution, marker starting energy, radial electric field strength, SOL flow and toroidal plasma rotation. The outcome comprises 13 simulations, each with 100, 000 markers. The findings are: Toroidal plasma movement, either within the LCFS or as SOL flow, is negligible. SOL profile and marker starting energy have modest impact on deposition. Source distribution has a large impact in combination with radial electric field profiles. The E ⇀ × B ⇀ drift has the highest impact on the deposition profiles.